Knowledge audit practices in electricity companies in Malaysia: A preliminary overview - Drus S.M.; Shariff S.S.M.; Othman M. (International Business Information Management Association, IBIMA, 2023)
Electricity supply industry plays an important role in ensuring that Malaysia is able to fulfil its aim of attaining the knowledge economy status. As one of the entities operating in electricity supply industry which is a knowledge-intensive industry, it is essential for electricity companies to effectively and appropriately manage and leverage their organisational knowledge. Effective management and utilisation of knowledge enable electricity companies to operate in the most optimal and efficient manner. Knowledge audit can be used as the mechanism to assist electricity companies to assess their current and future knowledge provisions and requirements. Examining the existing knowledge audit literature from Malaysian electricity supply industry's perspective, it is apparent that several issues may need to be addressed. Among the issues identified are i) none of the existing knowledge audit frameworks found in the literature have been applied in South East Asia; ii) only two (2) frameworks have been applied in electricity supply industry; iii) the frameworks only provide high-level descriptions and lack detailed and in-depth explanation on methods to conduct the audit; and iv) lastly, most of the existing frameworks do not show the link to the knowledge strategy of an organisation.